Ultrasensitive Detection of Plasma Amyloid-β as a Biomarker for Cognitively Normal Elderly Individuals at Risk of Alzheimer's Disease. - Chatterjee, Pratishtha; Elmi, Mitra; Goozee, Kathryn; Shah, Tejal; Sohrabi, Hamid R; Dias, Cintia B; Pedrini, Steve; Shen, Kaikai; Asih, Prita R; Dave, Preeti; Taddei, Kevin; Vanderstichele, Hugo; et al. (J Alzheimers Dis, 2019)
BACKGROUND: Aberrant amyloid-β (Aβ) deposition in the brain occurs two decades prior to the manifestation of Alzheimer's disease (AD) clinical symptoms and therefore brain Aβ load measured using PET serves as a gold standard biomarker for the early diagnosis of AD. However, the uneconomical nature of PET makes blood markers, that reflect brain Aβ deposition, attractive candidates for investigation as surrogate markers. OBJECTIVE: Investigation of plasma Aβ as a surrogate marker for brain Aβ deposition in cognitively normal elderly individuals. METHODS: Plasma Aβ40 and Aβ42 concentrations were measured using the ultrasensitive Single Molecule Array (Simoa) assay in 95 cognitively normal elderly individuals, who have all undergone PET to assess brain Aβ deposition. Based on the standard uptake value ratios (SUVR) obtained from PET imaging, using the tracer 18F-Florbetaben, plasma Aβ was compared between 32 participants assessed to have low brain Aβ load (Aβ-, SUVR <1.35) and 63 assessed to have high brain Aβ load (Aβ+, SUVR ≥1.35). RESULTS: Plasma Aβ42/Aβ40 ratios were lower in the Aβ+ group compared to the Aβ-group. Plasma Aβ40 and Aβ42 levels were not significantly different between Aβ-and Aβ+ groups, although a trend of higher plasma Aβ40 was observed in the Aβ+ group. Additionally, plasma Aβ42/Aβ40 ratios along with the known AD risk factors, age and APOEɛ4 status, resulted in Aβ+ participants being distinguished from Aβ-participants based on an area under the receiver operating characteristic curve shown to be 78%. CONCLUSION: Plasma Aβ ratios in this study are a potential biomarker for brain Aβ deposition and therefore, for preclinical AD. However, this method to measure plasma Aβ needs further development to increase the accuracy of this promising AD blood biomarker.

Association of Plasma Neurofilament Light Chain with Neocortical Amyloid-β Load and Cognitive Performance in Cognitively Normal Elderly Participants. - Chatterjee, Pratishtha; Goozee, Kathryn; Sohrabi, Hamid R; Shen, Kaikai; Shah, Tejal; Asih, Prita R; Dave, Preeti; ManYan, Candice; Taddei, Kevin; Chung, Roger; Zetterberg, Henrik; Blennow, Kaj; et al. (J Alzheimers Dis, 2018)
BACKGROUND: The disruption of neurofilament, an axonal cytoskeletal protein, in neurodegenerative conditions may result in neuronal damage and its release into the cerebrospinal fluid and blood. In Alzheimer's disease (AD), neurofilament light chain (NFL), a neurofilament subunit, is elevated in the cerebrospinal fluid and blood. OBJECTIVE: Investigate the association of plasma NFL with preclinical-AD features, such as high neocortical amyloid-β load (NAL) and subjective memory complaints, and cognitive performance in cognitively normal older adults. METHODS: Plasma NFL concentrations were measured employing the single molecule array platform in participants from the Kerr Anglican Retirement Village Initiative in Ageing Health cohort, aged 65- 90 years. Participants underwent a battery of neuropsychological testing to evaluate cognitive performance and were categorized as low NAL (NAL-, n = 65) and high NAL (NAL+, n = 35) assessed via PET, and further stratified into subjective memory complainers (SMC; nNAL- = 51, nNAL+ = 25) and non-SMC (nNAL- = 14, nNAL+ = 10) based on the Memory Assessment Clinic- Questionnaire. RESULTS: Plasma NFL inversely correlated with cognitive performance. No significant difference in NFL was observed between NAL+ and NAL- participants; however, within APOEɛ4 non-carriers, higher NAL was observed in individuals with NFL concentrations within quartiles 3 and 4 (versus quartile 1). Additionally, within the NAL+ participants, SMC had a trend of higher NFL compared to non-SMC. CONCLUSION: Plasma NFL is inversely associated with cognitive performance in elderly individuals. While plasma NFL may not reflect NAL in individuals with normal global cognition, the current observations indicate that onset of axonal injury, reflected by increased plasma NFL, within the preclinical phase of AD may contribute to the pathogenesis of AD.

Cerebral Glucose Metabolism is Associated with Verbal but not Visual Memory Performance in Community-Dwelling Older Adults. - Gardener, Samantha L; Sohrabi, Hamid R; Shen, Kai-Kai; Rainey-Smith, Stephanie R; Weinborn, Michael; Bates, Kristyn A; Shah, Tejal; Foster, Jonathan K; Lenzo, Nat; Salvado, Olivier; Laske, Christoph; Laws, Simon M; et al. (J Alzheimers Dis, 2016)
Increasing evidence suggests that Alzheimer's disease (AD) sufferers show region-specific reductions in cerebral glucose metabolism, as measured by [18F]-fluoro-2-deoxyglucose positron emission tomography (18F-FDG PET). We investigated preclinical disease stage by cross-sectionally examining the association between global cognition, verbal and visual memory, and 18F-FDG PET standardized uptake value ratio (SUVR) in 43 healthy control individuals, subsequently focusing on differences between subjective memory complainers and non-memory complainers. The 18F-FDG PET regions of interest investigated include the hippocampus, amygdala, posterior cingulate, superior parietal, entorhinal cortices, frontal cortex, temporal cortex, and inferior parietal region. In the cohort as a whole, verbal logical memory immediate recall was positively associated with 18F-FDG PET SUVR in both the left hippocampus and right amygdala. There were no associations observed between global cognition, delayed recall in logical memory, or visual reproduction and 18F-FDG PET SUVR. Following stratification of the cohort into subjective memory complainers and non-complainers, verbal logical memory immediate recall was positively associated with 18F-FDG PET SUVR in the right amygdala in those with subjective memory complaints. There were no significant associations observed in non-memory complainers between 18F-FDG PET SUVR in regions of interest and cognitive performance. We observed subjective memory complaint-specific associations between 18F-FDG PET SUVR and immediate verbal memory performance in our cohort, however found no associations between delayed recall of verbal memory performance or visual memory performance. It is here argued that the neural mechanisms underlying verbal and visual memory performance may in fact differ in their pathways, and the characteristic reduction of 18F-FDG PET SUVR observed in this and previous studies likely reflects the pathophysiological changes in specific brain regions that occur in preclinical AD.